On the Fractional PID Control of a Laboratory Servo System - Barbosa, Ramiro (2008)
In this paper are investigated several types of fractional-order PID controllers in the velocity control of a servo system. The fractional controller is more flexible and gives the possibility of adjusting carefully the dynamical properties of a control system. The servo system is controlled by using a real-time digital control system based on MATLAB/Simulink. Results are compared with those obtained from classical PID controllers. Experimental responses are presented and analyzed, showing the effectiveness of the proposed fractional-order algorithms.